An approximate analysis of tall building frames - Lau, I-kei; Tongchat Hongladaromp; Morino, Shosuke; Cook, David J.; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1975)
An approximate method for the analysis of tall building frames subjected to lateral loads is presented. To simplify the calculations, certain assumptions on the stiffnesses of the frame elements are made and all joint rotations on the same floor are assumed to be equal. Successive backward substitution process is employed in solving the governing equations for the unknown joint rotations at each floor. Several examples are shown to evaluate the accuracy and simplicity of the proposed method. Comparisons of the results are made with those obtained from other approximate methods and the results obtained from the more accurate method of matrix analysis. The comparisons indicate that the proposed method gives, in general, reasonably accurate results which can be used for the estimate of stiffnesses and preliminary design of building frames.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Tall buildings; Framing (Building)